2017
DOI: 10.1111/gcbb.12491
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from the energy crop oilseed rape (Brassica napus); the role of photosynthetically active radiation in diurnal N2O flux variation

Abstract: Oilseed rape (OSR, Brassica napus L.) is an important feedstock for biodiesel; hence, carbon dioxide (CO2), methane (CH4) and particularly fertilizer‐derived nitrous oxide (N2O) emissions during cultivation must be quantified to assess putative greenhouse gas (GHG) savings, thus creating an urgent and increasing need for such data. Substrates of nitrification [ammonium (NH4)] and denitrification [nitrate (NO3)], the predominant N2O production pathways, were supplied separately and in combination to OSR in a UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 84 publications
3
32
0
Order By: Relevance
“…Similar observations were made by Laville et al (2011) for a fertilized crop over a period of 9 days, while others found a correlation with deeper temperatures (Alves et al, 2012;Livesley et al, 2008). Keane et al (2017) observed a The daily pattern observed during the second and third peak episodes was less obvious (Table 4). On one hand, we observed larger night emissions than during the first peak episode, which could originate from a higher range of temperatures in May and June promoting nightly microbial activity.…”
Section: Daily Variation Of N 2 O Fluxessupporting
confidence: 77%
“…Similar observations were made by Laville et al (2011) for a fertilized crop over a period of 9 days, while others found a correlation with deeper temperatures (Alves et al, 2012;Livesley et al, 2008). Keane et al (2017) observed a The daily pattern observed during the second and third peak episodes was less obvious (Table 4). On one hand, we observed larger night emissions than during the first peak episode, which could originate from a higher range of temperatures in May and June promoting nightly microbial activity.…”
Section: Daily Variation Of N 2 O Fluxessupporting
confidence: 77%
“…Peak N 2 O fluxes were generally observed at the beginning of April (Figure 2(a-d)). Keane et al (2018) 651 g N ha −1 d −1 in WOSR fertilized, with ammonium nitrate and ammonium only, respectively. They observed an increase in N 2 O fluxes associated with higher levels of photosynthetically active radiation.…”
Section: Impact Of Tillage and N Rate On N 2 O Fluxesmentioning
confidence: 99%
“…The peak in N 2 O emissions seen here was equivalent to ca. 2000 µg m −2 hr −1 , which is more than ten times the magnitude of fluxes reported from Miscanthus in a long-term study at this site (Drewer et al, 2012) and approximately half the maximum rate seen at this farm following the addition of 120 kg N/ha ammonium nitrate fertilizer to oilseed rape (OSR, Brassica napus L.; Keane et al, 2018). While fluxes of a similar magnitude have been reported from unfertilized Miscanthus elsewhere (Guzman, Ussiri, & Lal, 2017), N 2 O emissions from established Miscanthus plantations are widely thought to be much lower than those from conventional cropping .…”
Section: High N 2 O Emission Eventmentioning
confidence: 67%
“…Whilst diurnal patterns of N 2 O emission have been seen several times before (e.g. Alves et al, ; Ryden, Lund, & Focht, ; Shurpali et al, ; Yamulki et al, ), and were very recently observed in OSR at the same farm (Keane et al, ), the diurnal variation reported by these authors was defined by a peak in emissions during the day and lower emissions during the night. The sole exception was reported by Shurpali et al (), who saw higher emissions at night under N‐limiting conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation